Türkiye’nin değişim yıllarında siyasi mizahla muhalefet örneği: marko paşa gazete - Vurucu, Sema Kahraman (My University, 2013)
TÜRKİYE’NİN DEĞİŞİM YILLARINDA SİYASİ MİZAHLA MUHALEFET ÖRNEĞİ:MARKO PAŞA GAZETESİ Bu çalışma, Türkiye’nin değişim yılları olarak adlandırılan 1945-1950 döneminin en etkili muhalefetini yapan siyasi mizah gazetesi Marko Paşa’yı, dönemin değişim dinamikleri ve basındaki diğer muhalif gazetelerin muhalefet anlayışları bağlamında incelemeyi amaçlamaktadır. Türkiye’nin, soğuk savaş sürecine paralel olarak şekillenen değişim yıllarının temel dinamikleri olan çok partili yaşama geçiş, Amerika ile gelişen ekonomik ilişkiler ile siyasi ve ekonomik liberalizasyon politikaları; dönemin “Tan-Vatan muhalefet cephesi” olarak adlandırılan tek parti iktidarına muhalif gazeteler ve literatür taramasıyla ortaya konulmaya çalışılacaktır. Bu bağlamda, soğuk savaş Türkiye'sinin siyasi ikliminin bir sonucu olarak yayın hayatına başlayan ve bu iklimde sol kesime yönelen baskıları tüm şiddetiyle yaşayan Marko Paşa gazetesinin, yayın hayatı üzerinden siyasi mizahla muhalefet anlayışı ve yaşadığı zorluklar irdelenecektir. yasi mizah, muhalefet, sansür, baskı, basın, siyaset

MARKO PAŞA NEWSPAPER: AN EXAMPLE OF POLITICAL HUMOUR DURING THE YEARS OR CHANGE IN TURKEY This study aims to examine the humor newspaper Marko Paşa, which was carrying out the most effective political opposition during the period between 1945-50, called Turkey’s years of change, through the dynamics of change in this era and within the context of the understanding of opposition among the other opposing newspapers. As the basic dynamics of the years of change, which were shaped in parallel with the Cold War period, the transition into multiparty political life, the economic relations developed with the U.S.A., and the policies of political and economic liberalization will be tried to be exposed through a literature survey and the newspapers called “Tan-Vatan opposition front’and opposed to the one-party government. In this context, by means of the publication life of Marko Paşa newspaper, which began to be published as a result of the political climate of the Cold War period Turkey and which fully felt the oppression directed at the leftists in this climate, the understanding of opposition through political humor and its difficulties will be examined. Key Words: political humor, opposition, censorship, oppression, press, politics
Keywords: Gazetecilik; Gazeteler; Siyaset ve Yönetim; Türkiye